A Charge Transport in Ultrathin Electrically Continuous Metal Films - Bigun, R.I.; Kunitsky, Yu.A.; Stasyuk, Z.V. (Наносистеми, наноматеріали, нанотехнології, 2010)
The problems of ultrathin stable electrically continuous metal films fabrication and their electron-transport properties are discussed. To prevent the coagulation process of metal grains during metal film condensation, the surfactant underlayers utilizing is discussed. Analysis of current theoretical concepts concerning electron-transport properties of metal film is performed. The experimental data are explained within the scope of the modern theoretical models.